A new basal beaded lacewing (Neuroptera: Berothidae) from mid-Cretaceous Myanmar amber. (March 2019) - Huang, Shuo; Ren, Dong; Wang, Yongjie
Abstract: A new genus and species of Berothidae, Protoberotha minuta gen. et sp. nov., is described from mid-Cretaceous Myanmar amber. Based on the comparisons of venational characters and female genital sclerites of the new genus with those of the extant berothids, it is concluded that the new genus had a close relationship with Cyrenoberothinae, representing a basal lineage of Berothidae. The structures of the female terminalia across the extant berothids are summarized and discussed.